Strategi dalam Meningkatkan Minat Baca Siswa dengan Literasi Digital dalam Pembelajaran - Nur Annisa; Putri Fazila Rahmi; Adrias , Adrias; Aissy Putri Zulkarnaini (Politeknik Kampar, 2025)
Digital technology has become a habit in human life. To face this digital era, an understanding of digital literacy is needed that can increase students' literacy skills. This study was conducted with the aim of describing a literature review on Strategies in Increasing Students' Reading Interest with Digital Literacy in Learning. This research method uses a literature review method. The data sources for this study are 5 journals in the last 5 years. The results of the study show that the 5 journals have differences, but there are similarities, namely regarding digital literacy. Digital literacy is an effective means of increasing the effectiveness of student learning if used properly and according to the goals to be achieved. The thing that distinguishes digital literacy from reading and writing literacy is the sources used by students in the form of reading sources.